The Paradoxical Origins of Modern Debt in Late Nineteenth Century Iceland. Revisiting the Landsbanki - Tryggvi Rúnar Brynjarsson 1992- (2015)
Instituted in 1885, the Landsbanki was intended to facilitate—among other things—the introduction of the mentality that can be called capitalistic rationality, a key prerequisite for the modern market economy. I explore in this essay what two Icelandic political thinkers and actors in the late nineteenth century, Tryggvi Gunnarsson and Arnljótur Ólafsson, wrote and said—in a remarkably explicit fashion—about these matters. This is a history that extends beyond the mere economics of debt, although that angle is not overlooked, and analyses the discourse on debt and debtors, with special emphasis on its moral dimension. Justice, honour, discipline, and trust are at the conceptual heart of this investigation. A bank’s lending policy is an ideal subject for examining the ideological tension between regulation and freedom, order and flux. It unveils thoroughly meditated expectations of how successfully people predict future wealth and everything which that valuation tacitly assumes: people’s tendencies to live above means, their abilities to safeguard investments from potential setbacks, and even the extent to which their free wills are handicapped by nature itself. Being a “worthy” debtor in the new, capitalistic Iceland meant being able to proactively contribute to the social goal that was economic growth induction. Our two main characters agree on this, but diverge thereafter. Arnljótur Ólafsson believed that any and all arbitration of “worth” should happen in the free marketplace. Tryggvi Gunnarsson, who became the Landsbanki’s chairman in 1893, considered the moral and social risks too high to justify lending to virtually anyone. The fact that a handful of fishing vessel owners in Southwest Iceland came out on top after the chairman had taken everything into account foreshadows (or so I argue) how a particular sector of the economy came to be its dominant force.